Taḥlīl Al-Akhṭhā’ Al-Lughawiyyah As-Syāi’ah ‘Alā Al-Mustawā As-Shautī Ladā At-Ṭhalibāt Min Al-Qism Al-I‘Dādī Bijāmi‘Ah Ar-Rāyah - Zakky Fathimah Muthmainah; Fahmi Ridha; Mada Wijaya Kusumah (Mauriduna: Journal of Islamic Studies, 2021)
يهدف هذا البحث إلى معرفة الأخطاء اللغوية الشائعة على المستوى الصوتي لدى الطالبات من القسم الإعدادي بجامعة الراية، ومعرفة أسبابها، ومعرفة الحلول المقترحة لعلاج تلك الأخطاء. اتبعت الباحثة المنهج الوصفي التحليلي، وقامت بملاحظة لغة الطالبات على المستوى الصوتي واختبار بعض الكلمات للحصول على الأخطاء الصوتية على عينة البحث بلغ عددها 44 طالبة من قسم الإعداد اللغوي بجامعة الراية. وقد أسفرت الدراسة إلى عدد من النتاج من أهمها: أن الطالبات يقعن في استبدال أصوات اللغة الإندونيسية بأصوات اللغة العربية لتأثرهن باللغة الأم, ومن تلك الأصوات: صوت /ع/ المنطوق بصوت /ء/, وصوت /ح/ المنطوق بصوت /ه/, والصوائت الطويلة المنطوقة بالصوائت القصيرة. ومن معظم أسبابها التدخل اللغوي، وعدم إيقاظ الوعي الصوتي, وعدم التركيز، والتطبيق الناقص للقاعدة, والتفاهم بين الناطقين باللغة الأم في الأخطاء الصوتية للغة العربية. والحلول المقترحة لعلاج تلك الأخطاء إلمام المعلمة التقابل اللغوي وتحليل الأخطاء، وإيقاظ الوعي الصوتي ويكون ذلك بالتعاون الفعال بين المدرسات والدارسات, وتوفير التغذية الراجعة بعد الممارسة على الفور، وتصحيح الأخطاء الصوتية بدون والتسامح بين الناطقين باللغة الأم. This study aimed to determine the common mistakes in pronunciation of Arabic sounds among the preparatory students at STIBA Ar-Raayah, to finds out the causes and to find out the proposed solutions to overcome these errors.This study used a descriptive analysis approach and to collect the data, and the researcher had taken a sample of reseach consisting of 44 female students from the preparatory class of STIBA Ar-raayah to make an arabic voice pronunciation test.The most important resulth of this study indicated that: some students at Ar-Raayah University are transferring some of characteristics of the Indonesian vowel and consonant sound in the oral performance of the Arabic language. These sounds include : sound /ع/ which is pronounced like sound /a/, sound /ح/ which is pronounced like /h/, and non-differentiation between short and long vowel pronunciation.As for the factors that cause these errors are linguistic overlap, lack of awareness to pronounce Arabic voices, lack of focus, the incomplete application of the rule, and tolerance in the vocal errors of the Arabic language between speakers. The suggested solutions to treat those errors are the familiarity of the teacher with the linguistic counterpart and analysis of errors, build awareness to pronounce Arabic voices which is done in effective cooperation between teachers and students, the provision of feedback immediately after the practice, and urgency of correct the sound errors without tolerance.